Perbedaan Pengaruh Pemberian Ekstrak Zingiber Officinale dengan Insulin terhadap Jumlah Anak Hidupa, Mati atau Resorbsi dan Cacat pada Rattus Norvegicus Model Diabetes Melitus Pragestasional - yasinta siskaningtia (Universitas Muhammadiyah Surabaya, 2018)
Diabetes mellitus was metabolic disease which had chronic hyperglycemic characteristic .The risk of fetal death and malformation which were higher in pregestational diabetes. The complications could be suppressed through insulin therapy. The reasons about insulin side effect made herbal therapy began to develop, such as ginger (Zingiber officinale). This research aimed to prove the difference effect of Zingiber officinale extract and insulin on the number of fetal dead or resorbsion, and malformations in Rattus novergicus model of pregestational diabetes mellitus. Thirty rats were divided into 1 negative control group and 4 groups which were modeled with type 1 DM with streptozotocin (STZ) i.p dose 50mg/kgBB in citrate buffer 0,05M pH 4,5. Rat with blood glucose levels >200mg/dL after 2 days of induction, were sampled and bundled. The treatment groups were given 1IU insulin, ginger extract 500mg/kgBB, and 1IU insulin plus ginger extract 500mg / kgBB. The 17th day of pregnancy fetal sample was observed macroscopically. Analysis data with One Way ANOVA and Post Hoc with LSD. There were significant differences in fetal malformation with p value was 0,012 and death or resorbsion were 0,001. Ginger extract could be used as a single therapy or combination therapy to reduced the number of fetal death or malformation.